HUBUNGAN KELENTURAN OTOT PUNGGUNG DENGAN HASIL HEADING PADA TEAM SEPAKBOLA BUNUT FC - Syaputra, Riki; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak: This study originated from the observation of researchers who conducted the bunut FC soccer team, that the players are heading in following the practice is still not good, this can be seen from the heading that players do not scalable to the maximum. The aim in this study was to examine the relationship of muscle spasticity heading back to the results on the football team FC bunut. The population was bunut FC soccer team totaling 19 people. Sampling techniques in using total sampling technique, in which the entire population be made in the sample. Data obtained from measurements of sit and reach and heading ability. Data were analyzed by using correlation produc moment. Based on the research that has been described in the previous chapter that of the 19 samples were performed in this study, and the data collected in the analysis by using correlation produc moment, so the result rhitung = 0,700> rtabel = 0.468 at a = 0.05. The conclusion of the analysis carried out that there is a significant relationship between the flexibility of the back muscles (X) to heading (Y) Bunut Soccer Team FC.Keywords: Muscle Flexibility Back, Heading2